164k views
2 votes
Figure T is the result of a transformation on Figure S. Which transformation would accomplish this? 6 -4 -3 2 3 Figure S Figure T -3 -4 -5

User Sprunth
by
4.9k points

1 Answer

1 vote

Let:


\begin{gathered} A=(1,-1) \\ A^(\prime)=(3,-2) \\ A\to(x+a,y+b)\to A^(\prime) \\ so\colon \\ 1+a=3 \\ a=3-1=2 \\ ---- \\ -1+b=-2 \\ b=-2+1=-1 \\ so\colon \\ A\to(x+2,y-1)\to A^(\prime) \end{gathered}

Therefore, the transformation T is:

A translation 2 units right and 1 unit down

User Roguebantha
by
5.4k points